PENGARUH PENDEKATAN CONCRETE PICTORIAL ABSTRACT BERBANTUAN GEOBOARD TERHADAP KEMAMPUAN SPATIAL SENSE SISWA SEKOLAH DASAR - Damayanti, Tika Yulia; Hafiziani Eka Putri; Erna Suwangsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this study was to investigate the value of spatial sense abilities in elementary school pupils. Students' spatial sense abilities are still regarded as lacking, most likely as a result of the way that present teaching approaches fail to encourage students' active construction of knowledge. The purpose of this study was to look into how students' spatial sense skills were affected and improved when the Concrete Pictorial Abstract (CPA) approach using geoboards was used. A sample of 56 fourth-graders from SDN Lebakgede participated in the study; 28 of the children in the experimental group received education utilizing the CPA technique with geoboards, while the remaining 28 students in the control group received traditional instruction using problem-based learning (PBL). A quasi-experimental design with a non-equivalent control group was used in the study. Two types of data were gathered for the study: test data (pretest and posttest) and non-test data (daily notebooks, observation sheets, and documentation). Descriptive and inferential analysis techniques were used to examine the data. When comparing students who got training using the CPA approach with geoboards to those who received traditional PBL education, the results showed a considerable improvement in spatial sense skills. Students' spatial sense skills improved when the CPA technique was used in conjunction with geoboards. Thus, the CPA method using geoboards might be seen as a useful substitute for instruction, particularly when teaching ideas of plane geometry to fourth-grade children.